The Imperative of research in medical education: A call to action for Pakistan - Shabbir, Ahmad; Ali Ahmad Khan,; Alina Mehmood, (Journal of the Pakistan Medical Association, 2025)
Dear Madam, We are primarily concerned with promoting the inclusion of research in Pakistani medical education, extending from classrooms to clinical practice. In almost every part of human life, ranging from social practices to healthcare, technology, and economics, research is essential in illuminating pathways and confronting the complex challenges of the 21st century. The development of novel therapeutic approaches, diagnostic instruments, and preventative measures relies on medical research, as these are critical for tackling the wide range of global health concerns that confront societies.1 Health workers can enhance patient outcomes by staying on the newest developments in diagnosis, treatment, and preventative techniques through research. Health practitioners are better equipped to deliver individualised, evidence-based care for each patient when they perform research because it deepens their understanding of diseases, the underlying mechanisms behind them, and the selection of effective interventions.2 The educational system in Pakistan, especially in the medical field, is confronting substantial challenges in an ever-changing global environment marked by constant innovations and research breakthroughs. Pakistan's educational system frequently lags behind due to outdated curricula and teaching techniques. This is in contrast to many inustrialised nations, where educational systems place higher priority on innovation, critical thinking, and hands-on learning experiences. Consequently, Pakistani medical school graduates find it more challenging to fulfil the demands of contemporary healthcare practices that could quickly adjust to changing circumstances when they join the industry. 3 Reforms that promote research education and incorporate it into undergraduate courses are necessary to improve Pakistan's medical education system. To provide students with practical training, it is imperative to include seminars and workshops in addition to specialized courses on research methods and critical thinking techniques. Furthermore, research projects must be incorporated into current curricula to promote participation and cross-disciplinary cooperation. Mentorship programs with experienced researchers and financing for student-led initiatives are essential steps.4 Diverse research opportunities will be made possible by the establishment of well-equipped research facilities and relationships with hospitals and public health organisations. Student involvement will be further encouraged by fostering a research culture through symposiums, prizes, and student-run groups. Faculty involvement in research can serve as an example for students, emphasising the importance of research in the advancement of medical knowledge. With the use of these interventions, we hope to develop a new generation of healthcare workers who are prepared to lead innovation and successfully tackle Pakistan's healthcare issues.